2016
DOI: 10.5296/jsr.v6i2.8749
|View full text |Cite
|
Sign up to set email alerts
|

Sociological Research on Teachers’ Emotions: Four Approaches and the Shared Themes

Abstract: During the mid-1990s, teachers' emotions emerged as an area of research in the sociology of education because many teachers all over the world were reported to be unhappy, dissatisfied, stressed, frustrated, and even alienated. This implies that teachers' emotions, especially negative ones, go beyond individual factors and have become a social issue. Therefore, researchers use sociological perspectives and theories to deepen our understanding of the phenomenon. In order to advance our understanding of the soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It has been revealed that most teachers all around the world feel negative in language learning classrooms, so it can be proposed that teachers’ emotions should go beyond emotional issues and should turn into social aspects. Thus, sociology can be considered as an agenda to be aware of the social foundations of teachers’ feelings ( Tsang, 2015 ). Lacking constructive emotions, teachers may not be interested or motivated to develop students’ academic, social, and emotional progress ( Day and Qing, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that most teachers all around the world feel negative in language learning classrooms, so it can be proposed that teachers’ emotions should go beyond emotional issues and should turn into social aspects. Thus, sociology can be considered as an agenda to be aware of the social foundations of teachers’ feelings ( Tsang, 2015 ). Lacking constructive emotions, teachers may not be interested or motivated to develop students’ academic, social, and emotional progress ( Day and Qing, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the past 30 years, researchers have predominantly used empirical studies (138, 89.61%) (e.g., Chen, 2017; Shami et al, 2017) which explain the substantial increase over the last 10 years. As noted, although being relatively small, a promising trend with regard to an increased number of conceptual/commentary studies (e.g., Miyagamwala, 2015; Tsang, 2015) were located in our review that somewhat balanced the wide range of article types. However, it also identified few expected review papers in Asia especially in the near future.…”
Section: Discussionmentioning
confidence: 82%
“…Fried, Mansfield and Dobozy (2015) argues that, when teachers employ emotion regulation in classroom setting, it could help them to improve positive emotions and reduce negative emotions. Tsang (2016) proposed two strategies that can be adopted by teachers to manage their emotions in the classroom setting, one strategy is surface acting and other is deep acting, thus surface acting can help teacher to reduce what could be expected in a particular situation in class regardless teacher's real emotions towards student, while deep acting help to change teacher feeling to match with appropriate emotional display in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%